Kesan globalisasi terhadap guna pakai undang-undang Islam di Malaysia - Shuaib, Farid Sufian (2016)
Globalization has influenced hegemonization of laws where the international laws has been apply in many countries. However, an issue pertaining to the challenges for international laws in Islamic countries has been given an attention due to the contradiction with Shariah law. Malaysia is not an exception in confronting this issues and challenges of globalization on the application of Islamic law in Malaysia. Therefore, the objective of this research is to make an exploratory analysis for the challenges in globalization to application of Islamic law in Malaysia. This research employed a qualitative legal research by analyzing the primary and secondary laws pertaining to the issues of globalization in the administration of Islamic law in Malaysia. The finding of this study is that the issues of the globalization has been raised where the some provisions in the international law are contradict with the norms of the application of Islamic laws in Malaysia as well as Shariah law.